2011
DOI: 10.1007/s10682-011-9473-y
|View full text |Cite
|
Sign up to set email alerts
|

Rapid experimental shift in host use traits of a polyphagous marine herbivore reveals fitness costs on alternative hosts

Abstract: The host breadth of any particular herbivore reflects a compromise between evolutionary forces that promote specialism and those that promote polyphagy. Because most terrestrial herbivorous insects specialize, explorations of this evolutionary balance have focused largely on specialist than on polyphagous herbivores. Here, we experimentally tested whether fitness-based tradeoffs in utilizing alternative hosts can be detected within a polyphagous marine herbivore. The marine amphipod Ampithoe longimana occurs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 83 publications
(74 reference statements)
0
4
1
Order By: Relevance
“…Unlike recent work in terrestrial systems in which cues from predatory spiders were found to alter grasshopper diet , the presence of predator cues did not affect A. longimana preference for D. menstrualis compared to a highly palatable alternative diet, U. linza (Fig. 7b; Sotka and Reynolds 2011). The observed interaction between predator and grazer treatments on primary production is not surprising given that, in the absence of grazers, predator cues had little overall effect on macro-and microalgae, while, in the presence of grazers, cues from treatments with pinfish (pinfish and three-predator species treatments) had generally positive effects on these producers (Fig.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Unlike recent work in terrestrial systems in which cues from predatory spiders were found to alter grasshopper diet , the presence of predator cues did not affect A. longimana preference for D. menstrualis compared to a highly palatable alternative diet, U. linza (Fig. 7b; Sotka and Reynolds 2011). The observed interaction between predator and grazer treatments on primary production is not surprising given that, in the absence of grazers, predator cues had little overall effect on macro-and microalgae, while, in the presence of grazers, cues from treatments with pinfish (pinfish and three-predator species treatments) had generally positive effects on these producers (Fig.…”
Section: Discussioncontrasting
confidence: 73%
“…However, increases in individual prey growth rates due to reduced resource competition in the presence of predators could have exacerbated our observed differences. 7b;Sotka and Reynolds 2011). Similarly, predators could affect prey morphology by reducing prey activity.…”
Section: Discussionmentioning
confidence: 99%
“…This endpoint was based on observable changes in algal growth among treatments and represented approximately two overlapping grazer generations [103]. Grazers were preserved in 70% EtOH and later identified and counted.…”
Section: Methodsmentioning
confidence: 99%
“…After 24 days we quantified treatment effects on grazer abundance, the biomass of all experimentally stocked macroalgae, and the accumulation of naturally colonizing algae (“microalgae”). This endpoint was based on observable changes in algal growth among treatments and represented approximately two overlapping grazer generations [103] . Grazers were preserved in 70% EtOH and later identified and counted.…”
Section: Methodsmentioning
confidence: 99%
“…3), and overlapping generations are implicit in the equation. We assumed generation time was equivalent between fish cue treatments (mean age of females at offspring birth = 14 days; Sotka & Reynolds, in press).…”
Section: Methodsmentioning
confidence: 99%